Strength Estimation of Teeth Reinforced with Different Types of Post Systems - RYNIEWICZ, Wojciech; RYNIEWICZ, Anna Maria; MADEJ, Tomasz; WIŚNIEWSKA, Grażyna (Engineering Transactions, 2017)
Posts are permanent, single-tooth and periodontal restorations. During chewing, forces make teeth with posts to undergo complex stresses. The aim of this work is to compare and estimate the upper medial incisors restored with custom posts and prefabricated composite posts reinforced with fibreglass using the finite element method. Modelling and numerical analyses provide the opportunity to evaluate the reconstruction of teeth using custom and prefabricated posts.